1977
DOI: 10.1042/cs052026pa
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lung Function and Mode of Inhalation on Penetration of Aerosol into the Human Lung

Abstract: . Effect of lung function and mode of inhalation on penetration of aerosol into the human lung. The method using radioactive tracer particles has been applied to study the effect of the mode of inhalation of aerosols on the depth of deposition in the lungs of 50 patients with airways obstruction. The findings show that the penetration of particles is directly related to: (1) volume inspired per breath (VI); (2) forced expiratory volume in one second (FEVY); and inversely related to (3) flow rate during inhalat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
2
6

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 6 publications
2
52
2
6
Order By: Relevance
“…RYAN et al [15] reported that aerosols deposit more peripherally during tidal breathing than with a single deep breath. There have been reports that once the aerosol has entered the lungs, deposition by impaction in large bronchi is more likely in patients with COPD, whose airways may be narrowed by a combination of bronchospasm, oedema and mucous hypersecretion [3,4,7], and that the penetration of particles is inversely related to flow rate during inspiration [3]. In the present study, inspiratory flow rate during inhalation tended to be lower in COPD patients than in normals.…”
Section: Discussionmentioning
confidence: 43%
See 3 more Smart Citations
“…RYAN et al [15] reported that aerosols deposit more peripherally during tidal breathing than with a single deep breath. There have been reports that once the aerosol has entered the lungs, deposition by impaction in large bronchi is more likely in patients with COPD, whose airways may be narrowed by a combination of bronchospasm, oedema and mucous hypersecretion [3,4,7], and that the penetration of particles is inversely related to flow rate during inspiration [3]. In the present study, inspiratory flow rate during inhalation tended to be lower in COPD patients than in normals.…”
Section: Discussionmentioning
confidence: 43%
“…It has been reported that the aerosol deposition within the lung in patients with COPD observed in a rectilinear scan is decreased compared with normal subjects [3,4]. In these studies, subjects inhaled aerosol with tidal breathing [4] or a limited inspiratory volume of <1 L [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The inhaled volume is increased and the aerosol penetrates deeply into the lung parenchyma. 103,104 To overcome the problem of actuationinhalation, coordination breath-actuated pressurized MDIs were introduced to the market. 105 Nevertheless, improved peripheral deposition was observed if patients did not hold their breath on completion of inhalation in comparison with pressurized MDIs that are not breath-actuated.…”
Section: Drug Delivery Systems Optimal Particle Sizementioning
confidence: 99%